Integrative Teaching Strategy for Developing Writing Skills in Non-Linguistics Master Students - E. A. Komochkina; L. V. Yarotskaya (Высшее образование в России)
The paper discusses some interdisciplinary, contextual, and linguistic aspects of developing language skills essential to writing scientific papers. The suggested strategy provides a theoretical foundation for designing an integrated teaching strategy that incorporates three basic components: teaching writing skills and subskills in a foreign language, using an online teaching platform, and the universality of the scientific language that underlies scientists’ professional communication all over the world. The paper identifies gaps in teaching writing skills in a foreign language, reveals typical mistakes, and proposes a way of their overcoming through introducing the integrative teaching strategy into the education process. The paper also focuses on some ways of implementing the strategy relative to the integration of traditional and online teaching of master students through their investigating specialist discourse elements, identifying formulaic expressions and grammar patterns with a view to using them in their profession-related discourse, learning to rely on those findings in producing a coherent text, and thus, developing their capacity to write clearly and effectively.